Blood Flow in Human Arterial System-A Review. (2016) - Thomas, Blessy; Sumam, K.S.
Abstract: The blood flow in human arterial system can be considered as a fluid dynamics problem. Simulation of blood flow in the arterial network system will provide a better understanding of the physiology of human body. Hence, hemodynamics play an important role in the development and progression of arterial stenosis, leading to the malfunctioning of cardiovascular system. Simulation studies of blood flow in the diseased condition can diagonise the health problem easily and also have many applications in the areas such as surgical planning and design of medical devices. This paper presents a review on the existing scenario of the simulation studies of blood flow, starting with a brief overview of the structure and function of arteries and veins followed by a discussion on pressure wave propagation, blood flow models and Fluid Structure Interaction in the arterial system.